2011
DOI: 10.1007/s10336-011-0663-8
|View full text |Cite
|
Sign up to set email alerts
|

Variation in baseline corticosterone levels of Tree Sparrow (Passer montanus) populations along an urban gradient in Beijing, China

Abstract: Rapid urbanization is a major anthropogenic pressure on bird species that rely on vegetation for food and shelter. Since the baseline corticosterone concentration (BCC) in some bird species has been found to increase slightly in response to environmental challenges, we hypothesized that urbanization could also induce an increase in BCC. To test this hypothesis, we compared the BCC of Tree Sparrow (Passer montanus) populations in five urban and two rural habitats and analyzed the relationship between BCC and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 37 publications
0
41
2
Order By: Relevance
“…Corticosterone release was also related to the degree of urbanization close to the catching site. Urbanization affects corticosterone regulation in other species as well [34][35][36] and a damped corticosterone response in urban areas may reflect habituation to stressors such as increased noise and human disturbance. Here, we used DCORT as an index of corticosterone regulation, rather than absolute levels of the hormone to control for individual variation in corticosterone regulation mechanisms (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Corticosterone release was also related to the degree of urbanization close to the catching site. Urbanization affects corticosterone regulation in other species as well [34][35][36] and a damped corticosterone response in urban areas may reflect habituation to stressors such as increased noise and human disturbance. Here, we used DCORT as an index of corticosterone regulation, rather than absolute levels of the hormone to control for individual variation in corticosterone regulation mechanisms (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results are mixed. For example, some studies reveal higher corticosterone levels (avian stress hormones) in urban compared to rural bird populations (Schoech et al, 2007;Fokidis et al, 2009;Zhang et al, 2011), whereas other studies found the opposite pattern or no significant differences (Partecke et al, 2006;French et al, 2008;AbolinsAbols et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A few but notable observations commonly show geographically explicit consequences of accelerating urban growth in China's cities: for instance, spatially shrinking and fragmentizing lake wetlands within Wuhan [33], gradually disappearing mangrove swamps with the expansion of urban areas to the shoreline in Shenzhen [34], changes in nest features of Magpies along the urban-rural gradient in Hangzhou [35], human settlement density-related fluctuations in baseline hormone levels in Beijing [36], decreased macroinvertebrate richness in stream habitats in relation to urban development level in the Qiantang River [37], and altered surface albedo owing to rapid urbanization [38]. All these observed changes and shifts seem to geographically coincide well with the dispersal of urban activities.…”
Section: Discussionmentioning
confidence: 99%